The vertical city: Design explorations on new typologies of high-rise architecture - Sarreshtedari, Samira (My University, 2023)
High-rise architecture is becoming more common around the world. The urgent need for more habitable and public space has led to an increasing number of tall buildings in cities that have a low average building height. Tall buildings have a large potential in generating space vertically from a smaller piece of land, making them a fundamental part of cities with increasing urbanization and densification. Today it seems that many tall buildings are concerned with striving for taller heights and dominance of a city’s skyline. Many of the tall buildings that are currently being built have monotonous floor plans extruded vertically with facades consisting of glass panels. The rapid increase of these repetitious tall buildings has sparked discussions and hesitations toward high-rise architecture. The purpose of this thesis is to understand the ongoing discussions of tall buildings and explore new typologies and potentials of high-rise architecture to reconceive the perception of what a tall building is and could be. The intention is to raise awareness of the potentials of tall buildings by showcasing a new perspective that provides with multifunctional components and has a reinvented expression. As tall buildings are a very current phenomena today, it is important to highlight the value that they can bring to a city. This thesis departs from mapping the history of tall buildings to understand the evolution of height in architecture over time. Research papers and reference projects are also studied to explore the ongoing discussions and advancements regarding contemporary tall buildings. The literature review results in design principles that drive the design explorations forward through several iterations focusing on geometry, structure and program. The knowledge gathered in this thesis ultimately results in an architectural design proposal of a tall building consisting of a vertical city, with the main focus being on reconceiving the traditional skyscraper typology.
Keywords: Skyscraper; Tall building; High-rise architecture; Vertical city